Low Back Pain Complaints of Online Ojek Drivers in Indramayu Regency in 2021 - Moch Sahrul Rizky; Tating Nuraeni; Tayong Siti Nurbaeti (Penerbit Hellow Pustaka, 2024)
Jobs as online motorcycle taxis attract a lot of public interest, but there are potential health problems for online motorcycle taxi drivers, one of the health problems is low back pain (lower back pain). This study was conducted to find complaints of low back pain in online motorcycle taxi drivers at the Indramayu Regency in 2021. This study used a cross-sectional design. The population in this study was 460 respondents. Samples were taken using purposive sampling of as many as 82 respondents. Measurement of Low back pain (lower back pain) using the Nordic body map. Data analysis was done by univariate, bivariate with chi-square test. The results of this study indicate that there are 56 respondents (68.3%) experiencing low back pain of moderate level. The results of the chi-square test showed that there was a significant relationship between years of service (p-value 0.00) and complaints of low back pain in online motorcycle taxi drivers in Indramayu Regency in 2021. In addition, the variables BMI (p-value 0.416), age (p-value 0.288), and smoking status (p-value 0.015) had no relationship with complaints of low back pain.